Update on Pharmacological Activities, Security, and Pharmacokinetics of Rhein. (18th August 2021) - Li, Gang-Min; Chen, Jun-Ren; Zhang, Hui-Qiong; Cao, Xiao-Yu; Sun, Chen; Peng, Fu; Yin, Yan-Peng; Lin, Ziwei; Yu, Lei; Chen, Yan; Tang, Yun-Li; Xie, Xiao-Fang; et al.
Abstract : Rhein, belonging to anthraquinone compounds, is one of the main active components of rhubarb and Polygonum multiflorum . Rhein has a variety of pharmacological effects, such as cardiocerebral protective effect, hepatoprotective effect, nephroprotective effect, anti-inflammation effect, antitumor effect, antidiabetic effect, and others. The mechanism is interrelated and complex, referring to NF- κ B, PI3K/Akt/MAPK, p53, mitochondrial-mediated signaling pathway, oxidative stress signaling pathway, and so on. However, to some extent, its clinical application is limited by its poor water solubility and low bioavailability. Even more, rhein has potential liver and kidney toxicity. Therefore, in this paper, the pharmacological effects of rhein and its mechanism, pharmacokinetics, and safety studies were reviewed, in order to provide reference for the development and application of rhein.